1991
DOI: 10.1093/infdis/163.2.226
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Disposition of Zidovudine during Pregnancy

Abstract: Zidovudine pharmacokinetics was determined in three human immunodeficiency virus type 1-seropositive women receiving zidovudine (200 mg orally every 4 h) from 19 to 39 weeks of pregnancy and postpartum. Zidovudine concentrations were measured using high-pressure liquid chromatography, and pharmacokinetic analyses were done using model-independent methods. For the pregnant versus postpartum periods, peak zidovudine levels (mean +/- 1 SD) were 3.9 +/- 1.7 mumol/l versus 4.3 +/- 0.04 mumol/l (P = .56); eliminatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
42
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(53 citation statements)
references
References 15 publications
9
42
0
Order By: Relevance
“…These data on the NRTIs zidovudine, lamivudine, stavudine, and didanosine show that they cross the placenta in HIVinfected pregnant women, in agreement with previous studies (12,14,15,25,26). Our study includes the first preliminary clinical data available on abacavir, which suggest that its placental transfer is also high.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These data on the NRTIs zidovudine, lamivudine, stavudine, and didanosine show that they cross the placenta in HIVinfected pregnant women, in agreement with previous studies (12,14,15,25,26). Our study includes the first preliminary clinical data available on abacavir, which suggest that its placental transfer is also high.…”
Section: Discussionsupporting
confidence: 92%
“…Zidovudine has been widely used and studied in pregnancy, and high cord-to-maternal plasma drug concentration ratios have been consistently reported (15,26). Similar results have been reported with lamivudine (12,14).…”
supporting
confidence: 58%
“…It is not yet known whether pregnancy affects the pharmaco kinetics of zidovudine. In one study, an increase in Vss and in zidovudine clearance during pregnancy was explained by the usual increase in body weight, plasma volume and renal and hepatic blood flow seen during pregnancy [21]. The pharmacokinetics of zidovudine were also monitored 3-4 weeks post partum and at that time the pharmacokinetic par ameters were no longer different from those re ported in HIV-infected men.…”
Section: Absorptionmentioning
confidence: 99%
“…Zidovudine distribution into saliva [20] is of particular interest because the ease of collection and avoidance of blood handling could make saliva a favourable matrix for therapeutic drug monitoring. Zidovudine crosses the placenta and has been measured in neonatal blood [21][22][23]. It is not yet known whether pregnancy affects the pharmaco kinetics of zidovudine.…”
Section: Absorptionmentioning
confidence: 99%
“…Although zidovudine did not always prevent vertical transmission of HIV (36), some studies showed that vertical transmission was not observed in a total of 11 cases who had been given zidovudine during pregnancy (37,38). These highly promising data, though preliminary, had been available at the time of protocol development of the PACTG 076 study (39).…”
Section: Questions From the View Of Contextual Featurementioning
confidence: 99%